The Value of Thoracic Computed Tomography Scans in Clinical Diagnosis: A Prospective Study - Mark O Turner; John R Mayo; Nestor L Müller; Michael Schulzer; J Mark FitzGerald (Canadian Respiratory Journal)
BACKGROUND: Computed tomography (CT) scans are used extensively to investigate chest disease because of their cross-sectional perspective and superior contrast resolution compared with chest radiographs. These advantages lead to a more accurate imaging assessment of thoracic disease. The actual use and evaluation of the clinical impact of thoracic CT has not been assessed since scanners became widely available.